Mesenchymal Stem Cell Immunomodulation: A Novel Intervention Mechanism in Cardiovascular Disease - Wang, Yueyao; Qi, Zhongwen; Yan, Zhipeng; Ji, Nan; Yang, Xiaoya; Gao, Dongjie; Hu, Leilei; Lv, Hao; Zhang, Junping; Li, Meng (Frontiers in Cell and Developmental Biology, 2022)
Mesenchymal stem cells (MSCs) are the members of pluripotent stem cells, which possess the capacity for self-renewal and multidirectional differentiation, and have several characteristics, including multilineage differentiation potential and immune regulation, which make them a promising source for cell therapy in inflammation, immune diseases, and organ transplantation. In recent years, MSCs have been described as a novel therapeutic strategy for the treatment of cardiovascular disease because they are potent modulators of the immune system with the ability of modulate immune cell subsets, coordinating local and systemic innate and adaptive immune responses, thereby enabling the formation of a stable inflammatory microenvironment in damaged cardiac tissues. In this review, we will review the current research progress of the immunomodulatory properties of MSCs and the underlying mechanisms, emphasizing the effect of these MSCs on immune cells, and then explain the therapeutic effects of this mechanism in the treatment of cardiovascular diseases and provide more feasible treatment guidelines in clinical applications.